The Effect of Accounting Information System Implementation on Internal Control Effectiveness in Sorong City MSMEs - Jalmijn Tindage; Tagor Manurung; Melda Agnes Manuhutu (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to analyze the effect of the application of Accounting Information Systems (AIS) on the effectiveness of internal control in Micro, Small and Medium Enterprises (MSMEs) in Sorong City. The background of this research is based on the need for MSMEs for a reliable financial management system and a control system that is able to minimize the risk of errors and fraud. The method used is an associative quantitative approach with multiple linear regression analysis techniques using SPSS. The population in this study were active MSME players in Sorong City, with a sample of 100 respondents selected through purposive sampling technique. The independent variables in this study consist of four dimensions of AIS, namely system reliability, ease of use, data security, and reporting accuracy. While the dependent variable is the effectiveness of internal control as measured through the five components of the COSO framework. The results showed that all AIS indicators simultaneously had a significant effect on the effectiveness of internal control. Partially, the accuracy of reporting is the dominant factor in influencing the effectiveness of internal control. The findings also highlight the importance of employee training and the role of information technology in supporting effective AIS implementation. Thus, the strategy to increase the effectiveness of MSME internal control must include strengthening information systems, increasing human resource capacity, and adaptive and sustainable digital transformation. This research provides practical implications for policy makers and MSME actors in managing more accountable financial governance.